Illness perceptions and quality of life among tuberculosis patients in Gezira, Sudan - Mohammed, Suleiman (Afr Health Sci, 2015)
AIMS: This study aimed to answer the following research question: What is the level of illness perceptions and quality of life among TB patients in Gezira state?. METHODS: A descriptive study design was used. Newly diagnosed smear positive TB patients registered in Gezira state in 2010 (n=425) formed the study population. The illness perceptions were measured by using Brief Illness Perceptions Questionnaire (BIPQ). Health Related Quality of Life (HRQoL) was assessed by means of the 12-item short form Health Survey questionnaire (FS-12). RESULTS: TB patients saw TB as having minor consequences, TB not being very well controlled by treatment, and TB as lasting long as a disease; they also associated several symptoms with TB. Furthermore, the patients had relatively poor physical and mental quality of life. Identity, consequences, personal control and emotional representations were associated with poor physical quality of life while concern about illness was associated with poor mental quality of life. CONCLUSION: The illness perceptions of the TB patients might influence their adherence to treatment. The poor quality of life of the TB patients in the different areas of quality of life such as daily activities and work, calls for programmes to strengthen TB information, education and counselling.